Habilidades Comunicativas para el Desarrollo del Lenguaje en los Niños de primer año paralelo F, de la Unidad Educativa Juan de Velasco, periodo académico 2017-2018 - Montalván Moreno, Inés Silvana (2018)
Nowadays, the actions of educational institutions require of research and proposals, which lead to the development of communication skills, according to the curriculum. The objective of this research is to determine the communication skills that help to the language development in the kids of first-year, these skills allow the human being to express their ideas, feelings and needs through language; These skills are speaking, reading, writing and listening, which strengthen the development of language in order to express in a coherent way. On the other hand according with the objectives given was demonstrated the development of language through communication skills activities such as: tongue twisters, stories, riddles; the broken phone game, telling stories, among others. The methodology used is descriptive and observation data sheets were used for data collection. As conclusion in this research it could see that kids in the development of communication skills are initiating this process, where were identified weaknesses by understanding messages, interacting with others, pronouncing sentences, among others; However, when working on activities that stimulate communication skills, their level is increased according to the development of the language; therefore, it is recommended to apply these activities.